2019
DOI: 10.3390/ma12244059
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage Properties of Self-Compacting Rubber Lightweight Aggregate Concrete: Experimental and Analytical Studies

Abstract: The shrinkage properties of self-compacting rubber lightweight aggregate concrete (SCRLC) were investigated by experimental and analytical studies in this paper. Rubber particles were used to substitute the sand in SCRLC by volume and rubber particles substitution percentages were 10%, 20%, 30%, 40% and 50%. The experimental results showed that the shrinkage strains of SCRLC increased with an increase of rubber particles substitution percentage. On the basis of China Academy of Building Research model and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Laboratory studies are a good way to start exploring new topics. In this research, laboratory studies using round and sharp-grained grains have been used to investigate the hypothesis of self-compacting materials in reality to study the effect of grain shape on self-compacting properties [18]. As mentioned in previous sections, this study examines cultivation experiments with real materials and compares the results of ideal and real materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies are a good way to start exploring new topics. In this research, laboratory studies using round and sharp-grained grains have been used to investigate the hypothesis of self-compacting materials in reality to study the effect of grain shape on self-compacting properties [18]. As mentioned in previous sections, this study examines cultivation experiments with real materials and compares the results of ideal and real materials.…”
Section: Methodsmentioning
confidence: 99%
“…Piles with a diameter of 48 inches were inserted into the alternative material and pulled out at low speed [16,17]. Figure 23 shows a schematic of the piling and a view of the piling operation at the port of Tombak, respectively [18].…”
Section: Limitations Of Choosing Land Improvement Methods Formentioning
confidence: 99%
“…The mix proportions of SCAC in this study, shown in Table 2, were calculated using Equation (1), in accordance with the Chinese standard JGJ 51-2002 [42]. The specimens that were subjected to quasi-static mechanical testing and dynamic mechanical testing were Φ50 mm × 100 mm and Φ65 mm × 35 mm cylindrical specimens, with 3 molded specimens in each group.…”
Section: Proportion and Sample Preparationmentioning
confidence: 99%
“…-Geotechnics (lightweight embankment fill, ground improvement, slope stability improvement, retaining wall construction, drainage and cut-off layers, road culverts) [28,29,[38][39][40][41]; -Technologies for the production of mineral and asphalt mixtures [28,29,33,42,43]; -Production of lightweight concretes [30,34,35,[44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%